2022
DOI: 10.1002/srin.202100843
|View full text |Cite
|
Sign up to set email alerts
|

A New Inert Gas Delivery Design for Improved Shielding of Ladle Shroud–Collector Nozzle (LS–CN) Assembly: Modeling, Design, and Industrial‐Scale Validations

Abstract: Argon injection in ladle shrouds is customarily practiced during the teeming of liquid steel from ladle to tundish to minimize air ingression and thereby restrict atmospheric oxidation of steel melt. Despite such practices, nitrogen pickup results in the tundish, implying inadequate shielding of ladle shroud-collector nozzle (LS-CN) joint. Accordingly, the efficacy of different argon injection designs in shrouds is evaluated in the present study, and thereby, a novel argon injection arrangement, embodying a tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…Figure 1 depicts a schematic of the molten steel transfer operation from a ladle to a continuous casting tundish via a ladle shroud. It is now rather well known [5][6][7][8][9] that due to aspiration of gases from the ambient (via slide-gate or shroud-collector nozzle joint), a two-phase, gas-liquid flow results in ladle shrouds. The phenomenon, particularly in the shroud, is shown to be driven by the low-pressure region prevalent inside a shroud during operation, assisted by various imperfections present at refractory artifacts joint/assembly.…”
Section: Process Descriptionmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 depicts a schematic of the molten steel transfer operation from a ladle to a continuous casting tundish via a ladle shroud. It is now rather well known [5][6][7][8][9] that due to aspiration of gases from the ambient (via slide-gate or shroud-collector nozzle joint), a two-phase, gas-liquid flow results in ladle shrouds. The phenomenon, particularly in the shroud, is shown to be driven by the low-pressure region prevalent inside a shroud during operation, assisted by various imperfections present at refractory artifacts joint/assembly.…”
Section: Process Descriptionmentioning
confidence: 99%
“…Special steel plants in India [3][4][5] 7-25 show relatively smaller nitrogen pick up (≈5 ppm) because beyond 200 s or so, shroud tip is completely submerged, and steel-air interaction in tundish tends to cease completely. [4] The latter value of nitrogen pickup can, therefore, be solely attributed to air-steel interaction in ladle shroud and hence applied toward a first-hand estimate of volumetric gas aspiration rate in shroud, relative to liquid flow rate (i.e., Q g /Q L ).…”
Section: Physical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some more recent work on physical and mathematical modelling by Mukherjee and Mazumdar [10][11][12] validated the use of full-scale water models to study Ladle Shroud systems, given that the Reynolds number similarity is maintained and the isothermal approach was validated [10]. The authors also found that homogenous argon shrouding distribution was not achieved by the studied argon delivery systems [11]. Additionally, a new delivery system, which delivered the argon tangentially, was proposed, resulting in enhanced shielding of the lower nozzle-Ladle Shroud joint [11].…”
Section: Introductionmentioning
confidence: 99%